Seed Priming With Melatonin Promotes Seed Germination and Seedling Growth of Triticale hexaploide L. Under PEG-6000 Induced Drought Stress - Guo, Yuhui; Li, Dongxiao; Liu, Liantao; Sun, Hongchun; Zhu, Lingxiao; Zhang, Ke; Zhao, Haiming; Zhang, Yongjiang; Li, Anchang; Bai, Zhiying; Tian, Liwen; Dong, Hezhong; et al. (Frontiers in Plant Science, 2022)
.Melatonin (N-acetyl-5-methoxytryptamine, MT) can mitigate abotic stress, including drought stress on a number of crops. However, it is unclear whether and how seed priming with melatonin alleviates the effects of drought stress on seed germination and seedling growth of triticale (Triticale hexaploide L.). In this study, we investigated the effects of seed priming with MT on seed germination, protective enzyme activity, superoxide anion, and hydrogen peroxide in triticale under PEG-6000 induced drought stress. Seed priming with 20 μM MT alleviated the adverse effects of PEG-6000 induced drought stress on seed germination and seedling growth. Triticale seeds primed with 20 μM MT exhibited improved germination potential, germination rate, germ and radicle length. Specifically, MT priming increased the germination rate by 57.67% compared with unprimed seeds. Seed priming with melatonin also alleviated the adverse effects of PEG-6000 induced drought stress on triticale seedlings. MT pretreatment with 20 μM significantly increased the net photosynthetic rate, transpiration rate, stomatal conductance, plant height, leaf area, and relative chlorophyll concentration, enhanced the activities of superoxide dismutase and peroxidase, and decreased reactive oxygen species (ROS) and malonaldehyde content in the seeds (germ and radicle) and seedlings (leaf and root). Collectively, these results suggest that seed priming with melatonin promotes ROS scavenging capacity and enhances energy supply and antioxidant enzyme activities to alleviate the adverse effects of drought stress in triticale.